Brain-gut interactions in obesity 2 - Pan, Weihong (Henry Stewart Talks, 2019)
Glial cells in the reaction and regulation of obesity, The gut as a large immune organ, and interface with the BBB, “Vascular, glial, and lymphatic immune gateways” of neuroimmune modulation, Metabolic changes of the BBB in obesity besides cytokine transport across the BBB, Implications in the pathophysiology of neurodegenerative diseases